Digital health in stroke: a narrative review - Gisele Sampaio Silva; João Brainer Clares de Andrade (Arquivos de Neuro-Psiquiatria)
Digital health is significantly transforming stroke care, particularly in remote and economically diverse regions, by harnessing mobile and wireless technologies, big data, and artificial intelligence (AI). Despite the promising advancements, a notable gap exists in the formal clinical validation of many digital health applications, raising concerns about their efficacy and safety in real-world clinical settings. Our review systematically explores the landscape of digital health in stroke care, assessing the development, validation, and implementation of various digital tools. We adopted a comprehensive search strategy, scrutinizing peer-reviewed articles published between January 2015 and January 2024, to gather evidence on the effectiveness of digital health interventions. A rigorous quality assessment was conducted to ensure the reliability of the included studies, with findings synthesized to underscore key technological innovations and their clinical outcomes. Ethical considerations were meticulously observed to maintain data confidentiality and integrity. Our findings highlight the transformative potential of mobile health technologies, AI, and telemedicine in improving diagnostic accuracy, treatment efficacy, and patient outcomes in stroke care. Our paper delves into the evolution and impact of digital health in cerebrovascular prevention, diagnosis, rehabilitation and stroke treatment, emphasizing the digital health's role in enhancing access to expert care, mitigating treatment delays and improving outcomes. However, the review also underscores the critical need for rigorous clinical validation and ethical considerations in the development and deployment of digital health technologies to ensure their safe and effective integration into stroke care practices.